MENINGKATKAN KARAKTERISTIK PESERTA DIDIK SEKOLAH DASAR MELALUI KEGIATAN MORNING ROUTINE - Wahyu Tri utami; Dini Rakhmawati; Arri Handayani (Kampus Akademik Publiser, 2024)
Abstract: The characteristics of students are very important for forming a good person, but what appears to be has not been implemented well in the school environment. The purpose of this research is to determine the importance of the teacher's role in developing students' character. The research method used is descriptive qualitative, namely describing the Morning Routine activities used by teachers to make it happen. The subjects studied were grade 4 students consisting of 13 students. The data collection techniques used are observation and interviews. From the results of observations, researchers found strategies used by teachers in implementing Morning Routine Activities, including; is memorization and habituation. From the results of research conducted by researchers, teachers have implemented the strategy well. This shows that teachers are good at understanding the character that must be applied to students. The teacher's role is very important in developing student character through Morning Routine activities in the form of habits, school culture, and school vision and mission. In the successful implementation of this strategy, teachers must creative in planning activities.Keywords: Student Characteristics, Morning Routine